Low-temperature environment-friendly composite modified asphalt for anti-cracking wearing layer and preparation method thereof
Patent Information
- Application Number
- CN202410293075.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-03-14
AI Technical Summary
[0004]在应用过程中,较高的拌合温度易造成材料受氧二次老化,降低沥青混合料的使用寿命,加剧生产过程中有害气体和粉尘的排放
[0038] 1. This invention uses a modifier to modify activated rubber powder, which can significantly improve the bonding ability of natural rubber powder. The molecular chain segments of the two can penetrate each other more deeply to form a good transition layer and achieve co-vulcanization, thereby improving the comprehensive properties of rubber powder such as wear resistance, resilience, tensile stress, hardness, tear strength, and aging resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering technology, specifically to a low-temperature environmentally friendly composite modified asphalt for crack-resistant wear-resistant layers and its preparation method. Background Technology
[0002] Crack-resistant wearing course technology is a preventative pavement maintenance technique that combines asphalt mixture with a waterproof bonding layer. It reliably addresses minor rutting, pavement cracking, whitening, and loosening, while also providing anti-skid, noise reduction, and improved pavement smoothness. This technology achieves the same performance as traditional pavements while reducing the thickness to 1 / 3 to 1 / 2 of the traditional asphalt overlay thickness. Based on a life-cycle economic benefit analysis of pavement assets, it can save 30-40% in construction and maintenance costs, demonstrating significant economic and social benefits.
[0003] Due to the reduced structural thickness, the tensile and shear stresses generated within the anti-cracking wear layer when it deforms under repeated wheel loads are greater than those of traditional asphalt overlays. Therefore, a high-viscosity asphalt should be used to provide stronger constraint on the aggregate skeleton to resist the relative movement and shear deformation between aggregate particles. It should also have high elasticity to recover deformation and resist the shrinkage and expansion effects caused by temperature differences, ensuring the overall stability and high-temperature stability of the wear layer, thereby avoiding common asphalt pavement defects such as loosening, shoving, and detachment.
[0004] During application, higher mixing temperatures can easily cause secondary aging of materials due to oxygen, reducing the service life of asphalt mixtures and exacerbating the emission of harmful gases and dust during production. In low-temperature environments, the rapid heat dissipation characteristic of traditional thin-layer asphalt mixtures can easily lead to a shortened effective construction time, reduced efficiency of manual and mechanical work, and extended construction periods.
[0005] Therefore, it is imperative to develop a modified asphalt that meets the outstanding advantages of high temperature and low viscosity, low temperature and high viscosity, good elasticity, and ease of routine construction of the anti-cracking and abrasion layer. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a low-temperature environmentally friendly composite modified asphalt for anti-cracking wear layer and its preparation method. The obtained composite modified asphalt has rheological properties of high viscosity at low temperature and low viscosity at high temperature, as well as good high-temperature stability and resistance to low-temperature cracking, which is conducive to low-temperature construction and has good application value and economic benefits.
[0007] The technical problem to be solved by this invention is achieved by the following technical solution:
[0008] One objective of this invention is to provide a low-temperature environmentally friendly composite modified asphalt, comprising the following raw materials in parts by weight:
[0009]
[0010] In a further technical solution, the petroleum asphalt is heavy cross-linked 70# petroleum asphalt or 90# petroleum asphalt.
[0011] In a further technical solution, the thermoplastic elastomer is a styrene-butadiene-styrene triblock copolymer with an average molecular weight of 90,000-150,000, a block ratio of 30 / 70-40 / 60, a number-average molecular weight of styrene at both ends of 10,000-20,000, an elongation at break of 600-800%, and a tensile strength of not less than 16 MPa. The purpose of using a low block ratio is to improve the low-temperature performance of the copolymer.
[0012] In a further technical solution, the tackifying resin is one or more of a resin and a polyisoprene derivative; the resin is one or more of an epoxy resin, a terpene resin, and a rosin-modified resin. Preferably, the tackifying resin is a compound composed of a resin and a polyisoprene derivative in a mass ratio of 2:1.
[0013] In a further technical solution, the modified activated rubber powder has an ash content of less than 15%, a carbon black content of more than 28%, a rubber hydrocarbon content of more than 52%, and an acetone extract content of 20-25%.
[0014] In a further technical solution, the modified activated rubber powder is obtained according to the following preparation method:
[0015] A. The rubber powder was activated using sodium hydroxide solution to obtain activated rubber powder;
[0016] B. Under the action of an initiator, the activated rubber powder is grafted and modified with a modifier to obtain modified activated rubber powder.
[0017] In this invention, step A removes dust and grease adhering to the surface of the rubber powder, and step B grafts and modifies the activated rubber powder to facilitate cross-linking with the resin polymer to form a spatial network structure.
[0018] In some specific embodiments, the mass concentration of the sodium hydroxide solution is 2-4%.
[0019] In some specific embodiments, the reaction temperature for graft modification is 80-90℃, and the reaction time is 3-5h.
[0020] In some specific embodiments, the modifier is a blend of FCC catalytic cracking slurry and maleic anhydride in a mass ratio of 3:7. The FCC catalytic cracking slurry contains light aromatics that soften rubber powder and increase the activity of carbon black in the rubber powder. The carboxyl groups in the maleic anhydride structure react with the hydroxyl groups in the activated rubber powder to form ester bonds, creating an ester crosslinking structure. This simultaneously enhances the adsorption capacity of the activated carbon black, forming a modified and activated sol-gel structure composition.
[0021] In some specific embodiments, the amount of the modifier is 7-13% of the mass of the activated rubber powder.
[0022] In some specific embodiments, the initiator is one or more of organic peroxide initiators and azo initiators, and the amount used is 0.2-0.6% of the rubber powder mass. In some specific embodiments, the initiator is benzoyl peroxide and 4,4-di(tert-butylperoxy)valerate n-butyl ester in a mass ratio of 1:1.
[0023] In a further technical solution, the modified surfactant is obtained by surface modification of the nano-surfactant powder using a silane coupling agent.
[0024] In some specific embodiments, the nanosurfactant is a mixture of nano-silica and nano-zirconia with a particle size of 10-15 nm and a mass ratio of nano-silica to nano-zirconia of 7:3.
[0025] In some specific embodiments, the mass ratio of the nano-surfactant powder to the silane coupling agent is 6:4.
[0026] In some specific embodiments, the silane coupling agent is silane coupling agent KH-550.
[0027] Nanosurfactants with high polarity, easy aggregation, and poor dispersibility can be better modified by surface modification to pre-modify activated rubber powder, resulting in high-performance activated rubber powder that is resistant to high temperature and aging.
[0028] In a further technical solution, the solubilizer is one or more of solvent oil, mineral base oil, and rubber oil.
[0029] In a further technical solution, the viscosity reducer is one or more of pyrolytic polyethylene wax and sugar alcohol monooleate. In some specific embodiments, the viscosity reducer is composed of 60-70% by weight of pyrolytic polyethylene wax and 30-40% by weight of sugar alcohol monooleate; the sugar alcohol monooleate is one or more of sorbitol monooleate and glyceryl monooleate.
[0030] The second objective of this invention is to provide a method for preparing the aforementioned low-temperature environmentally friendly composite modified asphalt, comprising the following steps:
[0031] (1) The modified activated rubber powder, modified surfactant and solubilizer are mixed and pre-swollen, and then heated to 150-170℃ for high-speed shearing to complete the pretreatment of the modified activated rubber powder.
[0032] (2) Heat petroleum asphalt to a fluid state, control the temperature at 180-190℃, then add thermoplastic elastomer, tackifying resin and viscosity reducer, shear at high speed, cool down to 150-160℃, then add pretreated modified activated rubber powder, shear at high speed, and finally cure and develop at 130-140℃ to obtain low-temperature environmentally friendly composite modified asphalt for crack-resistant wear layer.
[0033] In a further technical solution, the pre-swelling time is 30-60 minutes.
[0034] In a further technical solution, the high-speed shearing rate is 2000-4000 rpm, and the time is 0.5-2h.
[0035] In a further technical solution, the health-preserving and development time is 45-60 minutes, and the mixture is stirred once every 10-15 minutes to remove air.
[0036] The third objective of this invention is to provide the application of the aforementioned low-temperature environmentally friendly composite modified asphalt in the preparation of road surface anti-cracking and wear-resistant layers.
[0037] The beneficial effects of this invention are:
[0038] 1. This invention uses a modifier to modify activated rubber powder, which can significantly improve the bonding ability of natural rubber powder. The molecular chain segments of the two can penetrate each other more deeply to form a good transition layer and achieve co-vulcanization, thereby improving the comprehensive properties of rubber powder such as wear resistance, resilience, tensile stress, hardness, tear strength, and aging resistance.
[0039] 2. This invention modifies the surface of nano-surfactants, which better utilizes the high reactivity of nano-surfactants due to their large specific surface area and the presence of surface hydroxyl groups. This can compensate for the shortcomings of poor wetting and dispersion in organic phases caused by their strong hydrophilicity. Using coupling agent KH550 as a modifier, the nano-surfactants modified by in-situ liquid phase surface modification have good dispersion in rubber matrix, reduced agglomeration effect, and significantly improve the physical properties, wear resistance, and aging resistance of the matrix.
[0040] 3. This invention, through pretreatment of rubber powder, effectively solves the problem of rubber powder absorbing and fusing with lightweight components in asphalt during contact, but causing stress concentration at the low-temperature tensile interface due to the differences between rubber powder and asphalt, thus weakening the adhesion between asphalt particles. Furthermore, pretreatment can increase the amount of rubber powder in the asphalt, better achieving the modification effect.
[0041] 4. The tackifying resin used in this invention improves the low-temperature viscosity of asphalt through a combination of physical and chemical modification. Among them, epoxy resin, terpene resin, and rosin-modified resin have good miscibility with SBS, which together promotes the viscosity of the asphalt system. The main chain structure of the polyisoprene derivative is formed by the addition polymerization of small isoprene molecules. Its structural similarity with thermoplastic elastomers leads to the indiscriminate polymerization and cross-linking reaction of the broken small molecule chains under the synergistic effect of high-speed shearing and cooling operations. This allows the polyisoprene derivative to bridge the thermoplastic elastomer and asphalt molecules in a chemically modified manner to form a stable polymer system, thereby significantly improving the viscosity of the system.
[0042] 5. The viscosity reducer used in this invention has the characteristic of reducing the high-temperature viscosity of asphalt through phase transformation. When the temperature is above the melting point, it can be completely dissolved in the asphalt and promote the movement between polymer macromolecules or chain segments in the form of a surfactant, thereby increasing the distance between adjacent polymer molecules and reducing the van der Waals forces between chain segments, thus improving the workability of asphalt. When the temperature is below the melting point, it solidifies as a whole in the asphalt binder to form a spatial network structure, which improves the high-temperature stability and deformation resistance of the material. Detailed Implementation
[0043] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.
[0044] The following descriptions of the raw materials used in the examples and comparative examples are as follows:
[0045] The thermoplastic elastomer is a styrene-butadiene-styrene triblock copolymer with an average molecular weight of 100,000, a block ratio of 40 / 60, a number-average molecular weight of styrene at both ends of 13,000, an elongation at break of 800%, and a tensile strength of 18 MPa.
[0046] The tackifying resin is a compound composed of rosin-modified resin and polyisoprene derivative in a mass ratio of 2:1. The rosin-modified resin was purchased from Jiangxi Huajin New Materials Co., Ltd., and the polyisoprene derivative was purchased from Shanghai Saikerui Biotechnology Co., Ltd.
[0047] The rubber powder was purchased from Nantong Dahua Rubber Co., Ltd., with a mesh size of 40-60.
[0048] FCC catalytic cracking slurry was purchased from China Petroleum & Chemical Corporation Guangdong Branch.
[0049] The solubilizer was a mineral base oil purchased from Guangdong Hengyu Chemical Co., Ltd.
[0050] The viscosity reducer consists of 65% by weight of polypyrolyte wax and 33% by weight of sorbitol monooleate.
[0051] Modified activated rubber powder is obtained according to the following preparation method:
[0052] Rubber powder was placed in a 2.3% sodium hydroxide solution and stirred for 45 minutes. The mixture was then filtered, washed with water, and dried to obtain activated rubber powder. The activated rubber powder was then placed in toluene, dispersed evenly, and a modifier and initiator were added. The mixture was heated to 85°C and reacted for 3 hours. After the reaction was complete, the mixture was filtered, washed with maleic anhydride, and dried to obtain modified activated rubber powder. The modifier was a blend of FCC catalytic cracking slurry and maleic anhydride in a 3:7 mass ratio, and the amount of modifier was 10% of the activated rubber powder mass. The initiator was a mixture of benzoyl peroxide and 4,4-di(tert-butylperoxy)valerate in a 1:1 mass ratio, and the amount was 0.3% of the rubber powder mass.
[0053] The modified surfactant was obtained according to the following preparation method:
[0054] The nano-surfactant powder was dried at 100℃ for 24 h and then dispersed in 1-methyl-3-pyrrolidone. Silane coupling agent KH-550 diluted with 1-methyl-3-pyrrolidone was then added. The mass ratio of nano-surfactant powder to 1-methyl-3-pyrrolidone and silane coupling agent KH-550 was 3:5:2. The reaction was carried out at 60℃ for 4 h under nitrogen protection. After the reaction, the mixture was centrifuged, precipitated, and dried to obtain the modified surfactant. The nano-surfactant powder consisted of nano-silica and nano-zirconia in a mass ratio of 7:3, with a particle size of 10-15 nm.
[0055] Example 1
[0056] Preparation of composite modified asphalt:
[0057] 70 parts of 70# heavy-duty asphalt, 8 parts of thermoplastic elastomer, 5 parts of tackifying resin, 10 parts of modified activated rubber powder, 3 parts of modified surfactant, 5 parts of solubilizer, and 2 parts of viscosity reducer.
[0058] The specific preparation process includes the following steps:
[0059] (1) The modified activated rubber powder, modified surfactant and solubilizer are mixed and pre-swollen for 45 min, and the temperature is raised to 165℃. The mixture is sheared at a shear rate of 2000 rpm for 2 h to complete the pretreatment of the modified activated rubber powder.
[0060] (2) Heat 70# heavy-duty asphalt to a fluid state, control the temperature at 185℃, then add thermoplastic elastomer, tackifying resin and viscosity reducer, shear at a shear rate of 3000 rpm for 2 hours, cool down to 150℃, then add pretreated modified activated rubber powder, shear at a shear rate of 2000 rpm for 0.5 hours, and finally cure at 135℃ for 45 minutes, stirring once every 10 minutes to remove air, to obtain composite modified asphalt.
[0061] Example 2
[0062] Preparation of composite modified asphalt:
[0063] 70 parts of 70# heavy-duty asphalt, 10 parts of thermoplastic elastomer, 8 parts of tackifying resin, 15 parts of modified activated rubber powder, 6 parts of modified surfactant, 8 parts of solubilizer, and 5 parts of viscosity reducer.
[0064] The specific preparation process is the same as in Example 1.
[0065] Example 3
[0066] Preparation of composite modified asphalt:
[0067] 70 parts of 70# heavy-duty asphalt, 9 parts of thermoplastic elastomer, 8 parts of tackifying resin, 12 parts of modified activated rubber powder, 4 parts of modified surfactant, 8 parts of solubilizer, and 3 parts of viscosity reducer.
[0068] The specific preparation process is the same as in Example 1.
[0069] Example 4
[0070] Preparation of composite modified asphalt:
[0071] 70 parts of 90# heavy-duty asphalt, 10 parts of thermoplastic elastomer, 8 parts of tackifying resin, 15 parts of modified activated rubber powder, 6 parts of modified surfactant, 8 parts of solubilizer, and 3 parts of viscosity reducer.
[0072] The specific preparation process is the same as in Example 1.
[0073] Example 5
[0074] Preparation of composite modified asphalt:
[0075] 70 parts of 90# heavy-duty asphalt, 9 parts of thermoplastic elastomer, 7 parts of tackifying resin, 10 parts of modified activated rubber powder, 4 parts of modified surfactant, 6 parts of solubilizer, and 4 parts of viscosity reducer.
[0076] The specific preparation process is the same as in Example 1.
[0077] Example 6
[0078] Preparation of composite modified asphalt:
[0079] 70 parts of 90# heavy-duty asphalt, 8 parts of thermoplastic elastomer, 8 parts of tackifying resin, 15 parts of modified activated rubber powder, 6 parts of modified surfactant, 8 parts of solubilizer, and 5 parts of viscosity reducer.
[0080] The specific preparation process is the same as in Example 1.
[0081] Comparative Example 1
[0082] The difference between Comparative Example 1 and Example 2 is that rubber powder was used instead of modified and activated rubber powder, that is, the rubber powder was not activated or modified.
[0083] Comparative Example 2
[0084] The difference between Comparative Example 2 and Example 2 is that nano-surfactant was used instead of modified surfactant, that is, the surface modification treatment of nano-surfactant was not performed using silane coupling agent.
[0085] Comparative Example 3
[0086] The difference between Comparative Example 3 and Example 2 is that activated rubber powder was used instead of modified activated rubber powder, that is, no modifier was used to modify the activated rubber powder.
[0087] Comparative Example 4
[0088] The difference between Comparative Example 4 and Example 2 is that maleic anhydride was used instead of the modifier to modify the activated rubber powder, that is, FCC catalytic cracking slurry was not used as the modifier.
[0089] According to the industry standard "Test Procedures for Highway Asphalt and Asphalt Mixtures JTGE20-2011", the composite modified asphalt obtained in the above examples was tested for various performance indicators, including: ductility at 5℃, rotational viscosity at 100℃, dynamic viscosity at 60℃ after TFOT, penetration, softening point, ductility at 5℃, viscosity-toughness, toughness, and elastic recovery rate. The results are shown in Table 1.
[0090] Table 1 Performance Indicators of Composite Modified Asphalt
[0091] Table 1-1
[0092]
[0093]
[0094] Table 1-2
[0095]
[0096] As can be seen from Table 1, the viscosity of the composite modified asphalt prepared in Examples 1-6 at 100℃ is less than 3.0 Pa·s, and the dynamic viscosity at 60℃ after aging is higher than 140,000 Pa·s, indicating that it has the characteristics of high viscosity at low temperature and low viscosity at high temperature, good workability, and is easy to construct. The softening point of the residue after film heat aging (TFOT) is greater than 80℃, the ductility at 5℃ is greater than 45 cm, and the elastic recovery rate is greater than 90%, indicating that it has good high temperature stability and resistance to low temperature cracking.
[0097] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A low-temperature environmentally friendly composite modified asphalt, characterized in that, The ingredients include the following parts by weight: 70 parts of petroleum asphalt 8-10 parts of thermoplastic elastomer 5-8 parts of tackifying resin 10-15 parts of modified activated rubber powder 3-6 parts of modified surfactant 5-8 parts of solubilizer 2-5 parts of viscosity reducer; The modified and activated rubber powder is obtained according to the following preparation method: A. The rubber powder was activated using sodium hydroxide solution to obtain activated rubber powder; B. Under the action of an initiator, the activated rubber powder is grafted and modified with a modifier to obtain modified activated rubber powder; the modifier is a mixture of FCC catalytic cracking slurry and maleic anhydride in a mass ratio of 3:
7. The modified surfactant is obtained by surface modification of nano-surfactant powder using a silane coupling agent; the nano-surfactant is a mixture of nano-silica and nano-zirconium dioxide, with a mass ratio of nano-silica to nano-zirconium dioxide of 7:3; the silane coupling agent is silane coupling agent KH-550.
2. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The petroleum asphalt is heavy cross-linked 70# petroleum asphalt or 90# petroleum asphalt; the thermoplastic elastomer is a styrene-butadiene-styrene triblock copolymer with an average molecular weight of 90,000-150,000, a block ratio of 30 / 70-40 / 60, a number-average molecular weight of styrene at both ends of 10,000-20,000, an elongation at break of 600-800%, and a tensile strength of not less than 16 MPa.
3. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The tackifying resin is one or more of resins and polyisoprene derivatives; the resin is one or more of epoxy resins, terpene resins, and rosin-modified resins.
4. The low-temperature environmentally friendly composite modified asphalt according to claim 3, characterized in that: The tackifying resin is a compound composed of resin and polyisoprene derivative in a mass ratio of 2:
1.
5. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The modified activated rubber powder has an ash content of less than 15%, a carbon black content of more than 28%, a rubber hydrocarbon content of more than 52%, and an acetone extract content of 20-25%.
6. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The mass concentration of the sodium hydroxide solution is 2-4%.
7. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The grafting modification reaction temperature is 80-90℃, and the reaction time is 3-5 h.
8. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The amount of the modifier used is 7-13% of the mass of the activated rubber powder.
9. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The initiator is one or more of organic peroxide initiators and azo initiators, and the amount used is 0.2-0.6% of the mass of the rubber powder.
10. The low-temperature environmentally friendly composite modified asphalt according to claim 9, characterized in that: The initiator is benzoyl peroxide and 4,4-bis(tert-butylperoxy)valerate n-butyl ester in a mass ratio of 1:
1.
11. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The particle size of the nanosurfactant is 10-15 nm.
12. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The mass ratio of the nano-surfactant powder to the silane coupling agent is 6:
4.
13. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The solubilizer is one or more of solvent oil, mineral base oil, and rubber oil.
14. The low-temperature environmentally friendly composite modified asphalt according to claim 1, characterized in that: The viscosity reducer is one or more of pyrolyzed polyethylene wax and sugar alcohol monooleate.
15. The low-temperature environmentally friendly composite modified asphalt according to claim 14, characterized in that: The viscosity reducer consists of 60-70% by weight of pyrolyzed polyethylene wax and 30-40% by weight of sugar alcohol monooleate.
16. The low-temperature environmentally friendly composite modified asphalt according to claim 14, characterized in that: The sugar alcohol monooleate is one or more of sorbitol monooleate and glyceryl monooleate.
17. The method for preparing low-temperature environmentally friendly composite modified asphalt according to any one of claims 1-16, characterized in that, Includes the following steps: (1) The modified activated rubber powder, modified surfactant and solubilizer are mixed and pre-swollen, and then heated to 150-170℃ for high-speed shearing to complete the pretreatment of the modified activated rubber powder. (2) Heat petroleum asphalt to a fluid state, control the temperature at 180-190℃, then add thermoplastic elastomer, tackifying resin and viscosity reducer, shear at high speed, cool down to 150-160℃, then add pretreated modified activated rubber powder, shear at high speed, and finally cure and develop at 130-140℃ to obtain low-temperature environmentally friendly composite modified asphalt for crack-resistant wear layer.
18. The method for preparing low-temperature environmentally friendly composite modified asphalt according to claim 17, characterized in that: The pre-swelling time is 30-60 min.
19. The method for preparing low-temperature environmentally friendly composite modified asphalt according to claim 17, characterized in that: The high-speed shearing rate is 2000-4000 rpm, and the time is 0.5-2 h.
20. The method for preparing low-temperature environmentally friendly composite modified asphalt according to claim 17, characterized in that: The growth and development time is 45-60 minutes, and the mixture is stirred every 10-15 minutes to remove air.
21. The application of the low-temperature environmentally friendly composite modified asphalt according to any one of claims 1-16 in the preparation of road surface anti-cracking and wear-resistant layers.
Citation Information
Patent Citations
SBS modified anti-cracking pitch preparing method
CN105038268A
Reactive adhesive modified asphalt waterproof roll and preparation method thereof
CN105754359A